The Discourse of Primaries in American and Slavonic Linguo-Cultures - Gorina, E.V. (Харкiвський нацiональний унiверситет iм. В.Н. Каразiна, 2011)
Primaries are highly ritualized institutional practices, branched in the USA and new for Slavonic linguo-cultures. The discourse of primaries includes linguistic, cognitive and communicative or social-pragmatic aspects. Primaries – intermedial and polycode discourse, the unity of audio-visual and verbal line, gradual in its concrete speech genres.
Keywords: American and Slavonic linguo-culture; intermediality; polycode; the discourse of primaries